The use of micro-Raman spectroscopy to differentiate between sound and eroded primary enamel - FIONA GILCHRIST, ARIO SANTINI, KATHRYN HARLEY, & CHRISTOPHER DEERY (IAPD and Blackwell, 2007)
Erosion is the loss of dental hard tissue by a chemical process not involving bacteria , and this is a problem that has clinical significance. Data collected for the Children’s Dental Health in the United Kingdom 2003 survey showed that 53% of 5-year-olds had erosion affecting the lingual surfaces of their upper anterior teeth.